2007
DOI: 10.1080/00048670701332953
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Australians’ Understandings Regarding Mental Health and Disorders

Abstract: The purpose of the present paper was to determine what is currently documented about Indigenous Australians' understandings of mental health and mental disorders through a meta-synthesis of peer-reviewed qualitative empirical research. The following databases were electronically searched (1995-April 2006): AOA-FT and AIATSIS, Blackwell Synergy, CINAHL and Pre CINHAL, Health source: nursing/academic edition, Medline, Proquest health and medical complete, PsycInfo, Science Direct, Synergy and HealthInfoNet. Elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 34 publications
3
68
0
Order By: Relevance
“…4). A meta-synthesis of studies conducted with Aboriginal and Torres Strait Islander people found that attempts at defining mental health included elements of cultural, spiritual, social, and emotional well-being (Ypinazar et al, 2007). Ypinazar et al (2007) also noted that there is no single Aboriginal and Torres Strait Islander culture, and thus a definitive consensus regarding the definition of mental health has not yet been reached.…”
Section: Mental Health and Well-being For Children In Out-of-home Carementioning
confidence: 99%
See 1 more Smart Citation
“…4). A meta-synthesis of studies conducted with Aboriginal and Torres Strait Islander people found that attempts at defining mental health included elements of cultural, spiritual, social, and emotional well-being (Ypinazar et al, 2007). Ypinazar et al (2007) also noted that there is no single Aboriginal and Torres Strait Islander culture, and thus a definitive consensus regarding the definition of mental health has not yet been reached.…”
Section: Mental Health and Well-being For Children In Out-of-home Carementioning
confidence: 99%
“…2) Episodes of mental illness in the general population are initially treated in the primary health system or referred to mental health services for specialist treatment. Aboriginal and Torres Strait Islander experts stress the importance of a shared, cooperative approach to defining mental health for Aboriginal and Torres Strait Islander people (Ypinazar, Margolis, Haswell-Elkins, & Tsey, 2007). From an Aboriginal perspective, services should not just aim for an absence of the signs and symptoms of mental illness in an individual, but should "strive to achieve the state where every individual is able to achieve their full potential as a human being of their community" (NACCHO cited in Aboriginal Health and Medical Research Council of New South Wales, n.d., para.…”
Section: Mental Health and Well-being For Children In Out-of-home Carementioning
confidence: 99%
“…Potential explanations have included loss of cultural identity, intergenerational trauma caused by colonization and social exclusion. However, understanding of mental health problems in Aboriginal and Torres Strait Islander people remains unclear [9]. Differences in suicide rates compared with other Australians are particularly deep for early adolescents aged 10-14 years, with Indigenous Australians having over 12-times higher suicide rates [10].…”
Section: Discussionmentioning
confidence: 99%
“…They include quantitative research targeting demographic risk factors (Australian Bureau of Statistics, 2010) and environmental risk factors (Clough et al, 2004;Dingwall & Cairney, 2011;Gault, Krupinski, & Stoller, 1970;Lee et al, 2009;McKendrick et al, 1990) as well as qualitative research focused on social risk factors (Bostock, 1924;Cawte, 1963Cawte, , 1988Eley et al, 2007;Hunter, 1991;Petchkovsky & San Roque, 2002) and clinical practice (Hunter, 1993(Hunter, , 2004Peeters & Kelly, 1999;Turale, 1994;Ypinazar, Margolis, Haswell-Elkins, & Tsey, Indigenist academics strive to add to the knowledge acquired via the Western research paradigm so that policy, practice, and evaluation may be more socially and culturally informed with respect to Indigenous Peoples. Rigney (1999) emphasises the need to liberate Australian Indigenous knowledge from the control, storage, and extraction techniques inherent in the Western academic discourse.…”
Section: Background Research Methodologies and Policies For Indigenoumentioning
confidence: 99%